Strategi Pemenangan Stevi Harman dalam Pemilihan Anggota DPD RI Tahun 2024 : (Studi Kasus Kemenangan Stevi Harman di Kabupaten Manggarai) (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This study aims to analyze the winning strategy of Maria Caecilia Stevi Harman in the 2024 election of members of the Regional Representative Council (DPD) of the Republic of Indonesia in East Nusa Tenggara Province (NTT). As a newcomer and female politician, Stevi Harman managed to win the most votes, outperforming the incumbent candidates. The main focus of the research is to examine how it mobilizes the masses and builds effective political machines in local contexts. This study uses a descriptive qualitative approach with data collection methods through observation, in-depth interviews, and documentation. The results of the study show that Stevi Harman's winning strategy consists of four main steps: mission formulation, sub-strategy, goals, and target image. The practical strategies implemented include a direct and personal approach to voters, as well as the use of social media as a political communication tool. The success of the campaign was supported by Stevi's identity as a doctor, a politician's family background, and an authentic self-image that was close to the community. This research highlights the importance of adaptive communication strategies, the use of personal identity as political capital, and a relationship-based approach in winning voter votes. These findings contribute to the study of contemporary political strategies, especially in the context of non-partisan but competitive DPD member elections.